The Roles of TIF1γ in Cancer - Yu, Chengpeng; Ding, Zeyang; Liang, Huifang; Zhang, Bixiang; Chen, Xiaoping (Frontiers in Oncology, 2019)
Transcriptional intermediary factor 1 γ (TIF1γ), also known as TRIM33, RFG7, PTC7, or Ectodermin, is an E3 ubiquitin-ligase family member with a ring-box-coiled-coil region. It can regulate TGF-β/Smad signaling in two different ways in different cellular contexts. On one hand, TIF1γ can monoubiquitinate Smad4 to inhibit the formation of Smad2/3/4 nuclear complexes. On the other hand, TIF1γ can function as a cofactor of phosphorylated (p)-Smad2/3, competing with Smad4 to inhibit the formation of the Smad2/3/4 complex. In addition, TIF1γ has been reported to play a role in transcription elongation, cellular differentiation, embryonic development, and mitosis. As transforming growth factor-β (TGF-β) superfamily signaling plays an important role in the occurrence and development of cancer, and TIF1γ was reported to be involved in the regulation of TGF-β superfamily signaling, studies on TIF1γ during the last decade have focused on its role in the development of cancer. However, TIF1γ can function either as a tumor suppressor or promoter in different cellular contexts, yet there are few reviews focusing on the roles of TIF1γ in cancer. Hence, in this paper we systematically review and discuss the roles of TIF1γ in cancer. Firstly, we review the biological features, the regulatory mechanisms and the related signaling pathways of TIF1γ. Next, we illustrate the roles of TIF1γ in different tumors. We then provide a tentative hypothesis that explains the dual roles of TIF1 γ in cancer. Finally, we provide our viewpoint regarding the future developments of cancer research focusing on TIF1γ, especially in relation to the effects of TIF1γ on tumoral immunity.